Penyelesaian Sengketa Pertanahan Yang Dilakukan Oleh Kantor Pertanahan Kabupaten Ngawi - Dewi, Rizky Permata (Lentera Hukum, 2015)
The soil is part of the earth called the earth's surface. Along with the rapidly growing era, the rate of population growth and development in Indonesia is increasing, so the basic needs will be higher. However, the number of circles of soil is out of balance. This causes land compensation. As some cases exist in the territory of the Land Office of Ngawi Regency. This article examines the complete forms of land disputes conducted by the Ngawi Land Affairs Office. Based on the literature review, in practice, the overall typology of land disputes in the work area of ​​the Ngawi District Land Office in 2017 from various cases of disputes that are rights-free landings, double certificates, and court decisions are also included in typology relating to juridical data because The Company is related to the voting rights over land and business related to the region in the region of Ngawi Regency with acceptable tariff outside the court and the court. This article concludes with a suggestion to provide certainty and measures that society desires for the process under the effectiveness, efficiency, and legal consent. KEYWORDS: Land Dispute, Tipologies Land Dispute, Settlement of Land Dispute.